Behaviour of postural adjustments during stand-to-sit in subjects with stroke - Peixoto, Marta Regina Moreira (2021)
When performing the transition from standing to sitting, prior to beginning the task, there should be a variation in the level of activity of the postural muscles. This modification presupposes the maintenance of safety and efficiency during the executation of this postural transition, through early postural adjustments (EPAs) and anticipatory postural adjustments (APAs). In individuals after a stroke, there is na impairment of postural control and the characterization of these adjustments still needs to be investigated. To analyze the behaviour of postural adjustments in the transition from standing to sitting in individuals after a stroke. A cross-sectional observational study was carried out with 18 individuals after a single stroke in the middle cerebral artery territory. They were asked to perform the sequence from standing to sitting, and the timing of variation in activity of the soleus, medial gastrocnemius, anterior tibial, rectus femoris, bíceps femoris and gluteus maximus of the ipsilesional (IPSI) and contralesional (CONTRA) limbs was recorded using surface electromyography. For statistical analysis, descriptive statistics was used, using the median, 25th percentile and 75th percentile, to analyze the activity of each muscle, and the Wilcoxon test was used to compare limbs, with a significance level of 0.05. There were no variations in muscle activity in the temporal window corresponding to early postural adjustments. Regarding the variation in the temporal window of APAs, it was found most individuals exhibited, for most muscles undr analysis, a variation in the direction of activation, with statistically significant diferences being found between the IPSI and CONTRA limbs in the anterior tibialis [6 (-61; 35)] and [27 (-19; 44)], respectively (p=0.025); soleus [26 (39; 41)] respectively (p<0.001) and rectus femoris [17.5 (-43; 40)], respectively (p=0.001). In this study, it was not possible to observe variation in the muscular activity of the postural muscles, in the temporal line of early postural adjustments. In the temporal line of anticipatory postural adjustments, although there was variation in muscle activity, it occured after begining of movement and with muscle activation behavior in all mucles. The IPSI limb muscles varied their activity earlier than the CONTRA limb muscles, except for gluteus maximus.